Assessing the Systemic Effects of Two Different Doses of Intra-Articular Triamcinolone Acetonide in Healthy Dogs - Gamble, Lauri-Jo; Boesch, Jordyn M.; Wakshlag, Joseph J.; Frye, Christopher W. (VCOT Open, 2020)
Objective Osteoarthritis is a common cause of pain and dysfunction in dogs. Intra-articular (IA) corticosteroids have been used to treat human and animal osteoarthritis; however, their systemic effects have not been well documented in dogs. Therefore, our objective is to determine if a single IA triamcinolone acetonide (TA) injection, at two different doses, suppresses the hypothalamic–pituitary–adrenal axis, induces alkaline phosphatase (ALP), or causes other clinicopathological abnormalities in dogs.Study Design Six healthy female intact adult mongrel dogs from a research colony. For phase one, dogs were randomly assigned to injection of 0.25 mg/kg TA into the right (n = 3) or left (n = 3) stifle. Haematology, liver-related biochemistry and adrenocorticotropic hormone stimulation tests were conducted the day prior to injection and repeated on days 1, 3 and 7, and then weekly after injection until values normalized. Following a 2-week washout period, 0.5 mg/kg TA was injected into the contralateral stifle (phase two), and laboratory testing mimicked phase one.Results Mild, transient adrenocortical suppression occurred in both phases, beginning on day 1 and resolving by days 3 and 7 in phases one and two respectively. However, post-adrenocorticotropic hormone stimulation cortisol levels were never outside the normal range for either phase. Alkaline phosphatase activity increased on day 3 in phase two but remained within normal limits. Mild stress leukograms occurred on day 1 in both phases. No clinical abnormalities were noted throughout the study.Conclusion Systemic adverse effects following IA TA stifle injections at 0.25 mg/kg and 0.5mg/kg are unlikely.
Keywords: corticosteroid; joint; canine; safety